Management of Renal Cell Carcinoma With Extensive Caval Thrombosis Utilizing a Temporary Atrial Caval Filter Through a Combined Endovascular and Open Surgical Technique. (July 2021) - Fontana, Federico; Deho, Federico; Piacentino, Filippo; Curti, Marco; Capogrosso, Paolo; Coppola, Andrea; Cocozza, Eugenio; Tozzi, Matteo; Venturini, Massimo
The most common cause of neoplastic thrombotic infiltration of the inferior vena cava is renal cell carcinoma (RCC). In the present report we described a case of a patient with massive RCC and extensive neoplastic thrombosis reaching the retrohepatic tract of the inferior vena cava. After a discussion in a multidisciplinary team meeting we decided to perform a radical nephrectomy with vena cava thrombectomy along with the support of a novel removable vena cava filter in order to avoid thromboembolism during the surgical procedure. Furthermore, a preoperative renal artery embolization with a non-adhesive liquid embolic agent was performed ahead of the surgical procedure in order to reduce the risk of intraoperative bleeding. The surgical procedure performed the day after was based on a hybrid endovascular-surgical approach consisting in nephrectomy, liver derotation, cavotomy with the additional use of a novel temporary caval filter, thus reducing the risk of intraoperative thromboembolic dissemination.